A lifespan approach to understanding family caregiver experiences of a blood cancer diagnosis. Issue 1 (February 2022) - Kastrinos, Amanda L.; Fisher, Carla L.; Mullis, Michaela D.; Wollney, Easton; Sae-Hau, Maria; Weiss, Elisa S.; Bylund, Carma L.
Abstract: Objectives: The study examined the diagnosis experience of midlife family caregivers of a patient with a blood cancer, exploring similarities and differences between parent caregivers and adult-child caregivers. Methods: Participants were between 30 and 65 years old and were family caregivers of a living patient with acute myeloid leukemia, acute lymphoblastic leukemia, or lymphoma. We conducted semi-structured interviews with parent caregivers ( n = 20) and adult-child caregivers ( n = 19) and a thematic analysis of the interview data. Results: Both types of caregivers report the patient experiencing (1) mis- and missed diagnosis (facing delayed diagnosis or treatment and having symptoms dismissed or overlooked) and (2) emotional distress (being in shock and survival mode, struggling with uncertainty, and confronting mortality). Adult-child caregivers also experienced relational shifts in assuming control of their parent's care, sometimes despite geographic distance, and struggled to distribute the care burden among family members. Significance of results: Differences between the caregivers' experiences emerged based on the relational role and the patient's place in the lifespan. Findings can be used to inform the development of support resources to address the needs of each group.